Labor Market Representation in Quantitative Macroeconomic Models for Developing Countries : An Application to Cote D'Ivoire - Bodart, Vincent (IMF Working Papers; Working Paper ;, 1995)
This paper presents a quantitative macroeconomic model that accounts for key features of the labor market in developing countries. Primarily inspired by Cote d'Ivoire, the model contrasts a formal urban sector, where wages are rigidly fixed and employment is submitted to firms profit-seeking behavior, to urban and rural informal sectors, where wages are flexible and employment is affected by fluctuations in formal sector employment. Dynamic simulations assess the impact on key macroeconomic variables of a terms of trade improvement, a public wage decrease, and an exchange rate adjustment, highlighting the roles of rural-urban migrations and capital accumulation in the informal urban sector.